Feasibility of 3DP cob walls under compression loads in low-rise construction. (27th September 2021) - Gomaa, Mohamed; Vaculik, Jaroslav; Soebarto, Veronica; Griffith, Michael; Jabi, Wassim
Highlights: Basic mechanical properties of 3D-printed cob were experimentally quantified. Mechanical properties of 3DP cob are shown to be comparable to traditional (non-3DP) cob. A model technique for compression design is demonstrated using a limit-state framework. Loadbearing 3DP cob wall are shown to be feasible for residential construction up to 2 stories. Abstract: The rapid adoption of 3D-printing (3DP) technologies in construction, combined with an increased willingness to reduce environmental impact, has facilitated reapproaching earth materials for modern building industry. The feasibility of 3DP earth-based materials has been under investigation in recent years, with a particular focus on cob due to its favourable characteristics toward the 3DP process. Yet, there is a lack of definitive information on the construction of 3DP cob. Hence this paper investigates the structural feasibility of 3D-printed cob walls in low-rise buildings. The investigation involved experimental compression tests on 3DP cob samples to obtain key mechanical properties including the compressive strength and elastic modulus. These properties were then used as inputs for structural analyses with respect to three alternate types of 3DP cob wall patterns to evaluate their load-carrying capacity based on a limit-state design framework. Results from the analyses were implemented in modelling an idealised low-rise cob building covering a range of floor spans and wall heights. The analytical study found that 3D-printed walls have the potential to sustain gravity loads typical of residential construction. Further, since the 3DP material was shown to have similar mechanical performance to conventional (non-3DP) cob on the material scale, the 3D-printing process provides the opportunity to produce wall sections that are structurally more efficient than the solid section used in conventional cob construction. This results in lower material consumption, making 3DP cob attractive from the point of view of resource efficiency. An important outcome of the study is the demonstration of a model design technique for low-rise 3DP cob buildings that could be implemented as part of a broader optimisation procedure to satisfy structural and architectural design objectives.